Influence of work discipline on employee performance as mediation on work motivation at PT. Satria Utama Garut Regency - Kurnia, Fuad Maulana (Institute of Computer Science (IOCS), 2025)
Work discipline is a mediator in this study, this study compares the direct and indirect effects of work discipline on employee performance to improve employee performance through effective and efficient proofing, which is measurable based on output and company-standard operational procedures. Many research has shown that work discipline has an impact on employee performance and work motivation. Employee performance is also influenced by work motivation as well, and is considered that work motivation can mediate the work discipline on employee performance. Respondents in this study are all employees of PT. Satria Utama in Garut Regency. There are 118 employees in total, and path analysis is the technique used direct and indirect. The study's findings indicate that every variable falls within the